Genomic Analysis of Ciprofloxacin-Resistant Salmonella enterica Serovar Kentucky ST198 From Spanish Hospitals - Vázquez, Xenia; Fernández, Javier; Bances, Margarita; Lumbreras, Pilar; Alkorta, Miriam; Hernáez, Silvia; Prieto, Elizabeth; de la Iglesia, Pedro; de Toro, María; Rodicio, M. Rosario; Rodicio, Rosaura (Frontiers in Microbiology, 2021)
Salmonella enterica serovar Kentucky (S. Kentucky) with sequence type (ST) 198 and highly resistant to ciprofloxacin (ST198-CipR) has emerged as a global MDR clone, posing a threat to public health. In the present study, whole genome sequencing (WGS) was applied to characterize all CipR S. Kentucky detected in five Spanish hospitals during 2009 to 2018. All CipR isolates (n=13) were ST198 and carried point mutations in the quinolone resistance-determining regions (QRDRs) of both gyrA (resulting in Ser83Phe and Asp87Gly, Asp87Asn or Asp87Tyr substitutions in GyrA) and parC (with Thr57Ser and Ser80Ile substitutions in ParC). Resistances to other antibiotics (ampicillin, chloramphenicol, gentamicin, streptomycin, sulfonamides and tetracycline), mediated by the blaTEM-1B, catA1, aacA5, aadA7, strA, strB, sul1 and tet(A) genes, and arranged in different combinations, were also observed. Analysis of the genetic environment of the resistance genes revealed the presence of multiple variants of SGI1 (Salmonella genomic island 1)-K and SGI1-P, where all resistance genes except catA1 were placed. IS26 elements, found at multiple locations within the SGI1 variants, have probably played a crucial role in their generation. Despite the wide diversity of SGI1-K- and SGI1-P-like structures, phylogenetic analysis revealed a close relationship between isolates from different hospitals, which were separated by a minimum of two and a maximum of 160 single nucleotide polymorphisms. Considering that S. enterica isolates resistant to fluoroquinolones belong to the high priority list of antibiotic-resistant bacteria compiled by the World Health Organization, continuous surveillance of the S. Kentucky ST198-CIPR clone is required.